Clearing the Air to Address Pollution's Cardiovascular Health Crisis - Mark R. Miller; Mariachiara Di Cesare; Shadi Rahimzadeh; Marvellous Adeoye; Pablo Perel; Sean Taylor; Shreya Shrikhande; Kelcey Armstrong-Walenczak; Anoop S. V. Shah; César Damián Berenstein; Rajesh Vedanthan; Elvis Ndikum Achiri; et al. (Ubiquity Press, 2024)
Air pollution is a critical global health issue that significantly impacts cardiovascular health. The air pollutant PM2.5 (particulate matter with a diameter of 2.5 micrometres or less) has been positioned as a leading environmental risk factor for morbidity and mortality, especially from cardiovascular diseases (CVDs). Using data from the World Health Organization (WHO), Global Health Observatory, and the United Nations Environment Programme, we explored global trends in air pollution, with a focus on PM2.5 levels, the implications for cardiovascular health, and the policy measures aimed at reducing their impact. Despite progress in reducing pollution levels in high-income countries, global trends show a limited annual reduction in PM2.5 concentration. The analysis highlights disparities between regions, with low- and middle-income countries bearing the brunt of air pollution-related CVDs. In 2019 alone, ambient air pollution was responsible for approximately 4.2 million deaths worldwide. Of these, 70% were caused by CVDs, with approximately 1.9 million deaths from ischemic heart disease and 900,000 deaths from stroke. Policy gaps remain a challenge, with many countries lacking adequate legally binding air quality standards. We recommend the adoption of WHO air quality guidelines, enhanced monitoring of air pollution levels, and increased investment in interdisciplinary research to understand the full scope of air pollution's effects on cardiovascular health. Addressing the global cardiovascular crisis linked to air pollution will require coordinated efforts from policymakers, healthcare systems, and global health organisations.